Women of the Subcontinent - Ghazi, Inam ul Haq (Hawwa, 2015)
Recorded Arabic travel logs about Asia in general, and in particular the Subcontinent during the Golden Era, contain interesting narratives about women of the region. This paper surveys narratives by Arab travellers regarding woman and tries to constitute a portrayal that may emerge from their writings. The selected writings for this paper cover 8 centuries (7th to 14th centuries ad) and the Subcontinent including modern-day countries of Pakistan, India, Bangladesh, Maldives and Sri Lanka. The picture that emerges from this study depicts various aspects about the women of Sub-Continent during these centuries. The most important aspects are: the role of women in society, their legal status and marriage, descriptions of beauty, women’s festivals, slavery, fashion and dresses for various occasions, and women from different classes, castes and religions. An attempt has been made to compare and contrast these narratives among themselves.